A rapid screening test by the latex antistreptolysin O test for streptococcal infections in CMS Teaching Hospital, Bharatpur, Nepal - Dewasy, BL; Singh, YI; Jha, BK; Kapil, J (Journal of College of Medical Sciences-Nepal, 2010)
Streptococcus pyogenes (group A Streptococci) infection is diagnosed by either bacterial culture or serological test. For the serodiagnosis, antistreptolysin O (ASO) and antideoxyribonuclease B (DNAase B) are the most widely accepted tests. To measure the antibodies (ASO) of Streptococcus with the help of Rapitex antistreptolysin as a screening test is widely used in cases of suspected streptococcal infections and its sequelae. There were 4230 serum samples of rheumatic fever, glomerulonephritis, rheumatic heart disease and rheumatic arthritis. They were tested for Antistreptolysin O (ASO) antibodies by latex agglutination test. The test is very simple, cheap, rapid, convenient and reliable. Correlation with the clinical diagnosis is possible for routine use. Key Words: ASO; rheumatic fever; latex agglutination DOI: 10.3126/jcmsn.v6i2.3613 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 24-28